DyAna - for 3 dimensional analysis of human motion - Baudin, J. P.; Gervais, P. (1995)
A 14 segment, rigid link model was used to represent the human body for this research. The 14 segments used in the model were the; trunk, head, neck, and right and left arms, forearms, hands, thighs, legs, and feet. The MIT Human Scale 1/2/3 data of Diffrient et al. (1974) was used to calculate the mass and the location of the center of mass for each segment. The principal mass moments of inertia for each link were calculated by normalizing the data, from Whitsett (1963) using the methods of Dapena (1978). The motions studied were the tuck jump, split jump and straddle jump and data was collected with two SVHS video cameras operating at 60 fields per second. The endpoints of each segment were then digitized using the Ariel Performance Analysis System. The Direct Linear Transform (DLT) technique was then used to transform the two views of two dimensional coordinates into three dimensional coordinates. These coordinates were then smoothed using a quintic spline and subsequently stored in an ASCII format along with the appropriate body segment parameters. This data file was used as input for the computer program DyAna which was written in 'C' and developed to perform a three dimensional kinetic and kinematic analysis of the motion. In general, the computer program DyAna was found to work well for doing a three dimensional kinetic and kinematic analysis of human movement for the airborne motions studied. Its best application in the field of biomechanics is in the study of human motion outside of the lab setting, such as in sporting events when subject preparation is not possible. It is presently being implemented in the study of gymnastics and figure skating skills. Future versions of the software will permit inclusion of external forces acting on the body.